Legalisasi Usaha dan Kesadaran Hukum Pelaku UMK Binaan UMKM Juara di Kecamatan Cisalak-Tanjungsiang - Hidayat, Agi Attaubah; Anwari, Amalia Nur; Sugiarti, Lilis Diah; Ikhsan, Fachrial; Saebani, Beni Ahmad (Al-Muamalat Jurnal Hukum dan Ekonomi Syariah, 2025)
This study aims to explore the legal awareness of MSME actors in business legalization under the guidance of the UMKM Juara program by the West Java Provincial Government in Kecamatan Cisalak-Tanjungsiang. The research adopts a juridical-empirical method with data collected through semi-structured interviews and literature studies to understand the perceptions and motivations of MSME actors regarding business legality. The findings reveal that although MSME actors generally understand the importance of business legality, they are often reluctant to pursue it, as it is perceived to provide no direct benefits. The primary motivation for legalization is driven by the need for halal certification, rooted in religious values. However, the lack of information on legalization procedures and limited support in guidance are the main obstacles. Social, cultural, and religious factors significantly influence legal awareness and the legalization process among MSMEs in the area.